Pain and the pathogenesis of biceps tendinopathy - Raney, Elise B (Am J Transl Res, 2017)
Biceps tendinopathy is a relatively common ailment that typically presents as pain, tenderness, and weakness in the tendon of the long head of the biceps brachii. Though it is often associated with degenerative processes of the rotator cuff and the joint, this is not always the case, thus, the etiology remains considerably unknown. There has been recent interest in elucidating the pathogenesis of tendinopathy, since it can be an agent of chronic pain, and is difficult to manage. The purpose of this article is to critically evaluate relevant published research that reflects the current understanding of pain and how it relates to biceps tendinopathy. A review of the literature was conducted to create an organized picture of how pain arises and manifests itself, and how the mechanism behind biceps tendinopathy possibly results in pain. Chronic pain is thought to arise from neurogenic inflammation, central pain sensitization, excitatory nerve augmentation, inhibitory nerve loss, and/or dysregulation of supraspinal structures; thus, the connections of these theories to the ones regarding the generation of biceps tendinopathy, particularly the neural theory, are discussed. Pain mediators such as tachykinins, CGRP, and alarmins, in addition to nervous system ion channels, are highlighted as possible avenues for research in tendinopathy pain. Recognition of the nociceptive mechanisms and molecular of biceps tendinopathy might aid in the development of novel treatment strategies for managing anterior shoulder pain due to a symptomatic biceps tendon.